International education and development culture, context and narrative - Stephens, David (Routledge, 2019)
Drawing on a wide range of international contexts, International Education and Development provides an innovative and comprehensive critique of developments to improve schooling in the global South. Offering both a theoretical critique of the field and a series of case studies, drawn from recent research, illustrating the usefulness of a narrative approach, it generates a greater understanding of the meta-narratives that shape development and international education. Focusing on three periods of extensive field work in South Africa, Bangladesh and Mauritius, this book reflects upon the combination of narrative and biographical approaches in different national settings. Context is provided in three levels, meta, meso and micro, through a clear and critical examination of the macro 'stories' of development and international education over the past fifty years, and an examination of the role that narrative can play at local and micro levels, looking at the stories of individual decision makers - from children in the classroom to education officers at the district education office - and the opportunities and challenges of using these accounts for research, teaching and policy-making purposes. International Education and Development adds a global perspective to an area dominated by a concern with the Northern industrialised world, making it an essential text for students following courses in the social sciences, and individuals working the field of international education. It addresses a fundamental concern of development theory in a unique and engaging manner. A highly original contribution to a growing field, this book synthesises developments both in this field and in the growing topic of narrative research
Keywords: Education / Social aspects / Southern Hemisphere / Case studies; Education / Social aspects / Developing countries / Case studies; Educational anthropology / Southern Hemisphere / Case studies; Educational anthropology / Developing countries / Case studies; Education and state / Developing countries / Case studies; Education and state / Southern Hemisphere / Case studies